Using the Internet in Improving Professional Capabilities of Professional Teachers - Uda, Tonich; Alexandro, Rinto; Oktaria, Merisa; Yenasadieni, Yenasadieni (Budapest International Research and Critics University, 2021)
The use of the internet in education, especially by students, has become a necessity for students. The internet provides a lot of information, knowledge, and materials for learning according to their individual needs. The purpose of this study is to describe the use of the Internet in Improving the Professional Ability of Prospective Teachers of Economic Education Study Program FKIP University of Palangka Raya. The method used in this study is a qualitative method, namely a research method that aims to describe a problem clearly. The types of data used are primary data and secondary data. Data collection techniques are through observation, interviews, and documentation. Data analysis was carried out using qualitative data analysis techniques consisting of three stages of activities carried out sequentially, namely data reduction, data display and conclusion drawing/verification. The results of this study indicate that the use of the internet by students of the Economics Education Study Program FKIP University of Palangka Raya is a necessity for them to obtain information, knowledge, learning materials that they do not get when studying in class with lecturers due to time constraints. The use of the internet also helps them to do their homework.